A prospective study of measured body size and height and risk of keratinocyte cancers and melanoma. (February 2016) - Lahmann, Petra H.; Hughes, Maria Celia B.; Williams, Gail M.; Green, Adèle C.
Highlights: We examined the association of anthropometric measures and incidence of skin cancers. Height is significantly associated with squamous cell carcinoma (SCC) development in men. Taller women present higher risk of basal cell carcinoma (BCC). Height seems to be positively associated with risk of melanoma in men. Body mass and body surface area appear unrelated to risk of skin cancers. ABSTRACT: Background: The potential influence of measured body weight and height on keratinocyte skin cancer risk has scarcely been studied. Some evidence indicates melanoma risk increases as self-reported height increases, but an association with body mass index (BMI) is less certain. Methods: We measured body weight and height of 1171 Australian men and women in a community-based skin cancer study in Queensland and prospectively examined the association of BMI, body surface area (BSA) and height and incidence of basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and melanoma while accounting for skin phenotype, sun exposure, clinical/cutaneous signs of chronic photodamage and other risk factors. Results: During 16 years of follow-up, 334 and 188 participants newly developed BCC and SCC, respectively; 28 participants were diagnosed with primary melanoma. BMI and BSA were unrelated to skin cancer incidence. After full adjustment, height was significantly associated with SCC development in men (relative risk (RR) = 1.66; 95% confidence interval (CI) = 1.11–2.48, for ≥175 cm vs ≤171 cm, P trend  = 0.017), and BCC in women (P trend  = 0.043). Melanoma in men, was similarly positively associated with height (RR per 5 cm increment = 1.55; 95%CI 0.97–2.47, P  = 0.067) though not significantly. Conclusion: This study shows that after adjusting for sun exposure tall stature may be a risk factor for the most common types of skin cancer BCC, SCC, and melanoma, while body mass and surface area appear unrelated to risk.